Problem driven innovation design strategies research for product manufacturing process - Qian Zhao; Haiyang Wang; Xin Guo; Qiongyuan Zhang; Hong Zeng; Xianglong Li; Kai Zhang (Scientific Reports)
Abstract As a prerequisite and foundation for production and manufacturing, the design of product manufacturing process plays a crucial role in improving production efficiency, controlling resource consumption, shortening production cycles, and reducing processing costs. With the rapid development of advanced manufacturing technologies, product manufacturing process design is increasingly characterized by ambiguity, multi-solution possibilities, and cross-disciplinary integration, posing higher demands on enterprises’ capabilities in process design and innovation. To identify and innovatively address these issues within complex product manufacturing process, this study proposes a problem-driven innovation design strategy model for product manufacturing process. In the problem identification phase, opportunities are identified and categorized based on the product context and manufacturing process, followed by problem identification and the construction of problem elements using problem analysis methods. After identifying the problems, the type of innovation required is determined, and corresponding methods are applied to generate a set of solutions with innovation potential. These solutions are then evaluated and validated to determine the optimal innovation design for the product manufacturing process. If a solution fails validation, the problem is re-identified or re-solved, and the above steps are repeated until a validated final solution is achieved. Finally, the feasibility of the proposed strategy is demonstrated through a case study on the innovation design of the wax pattern manufacturing process for gas turbine blades.